The Role of Values in Maintaining Ecological Balance in New Uzbekistan - Xudaynazarov Samad Xudayberdievich (Indonesian Journal Publisher, 2025)
This article explores the role of values in maintaining ecological balance in New Uzbekistan. In the article, environmental values are understood as beliefs, principles and practices aimed at respect for nature, rational use of resources and Environmental Protection. The article will analyze the environmental policies and strategies of the New Uzbekistan, including measures for the transition to a